CURRENT PROCESS AND ADVANTAGES OF PRIVATIZING AND TRANSFORMING STATE-OWNED BANKS IN UZBEKISTAN (World Bulletin of Management and Law, 2025)
The scientific article considers the advantages of privatization and transformation in the banking system, the comparison of the activity and profitability of state banks and private commercial banks in competitive market conditions, as well as the activities carried out in this regard in our country and the banking system in neighboring countries. In our country, presidential decrees on the reform of the banking system have been adopted, and great opportunities are being created for the development process